Resting-state connectivity deficits associated with impaired inhibitory control in non-treatment-seeking adolescents with psychotic symptoms - GARAVAN, HUGH; DONOHOE, GARY (My University, 2014)
Objective— Psychotic symptoms are common in the population and index risk for a range of severe psychopathological outcomes. We wished to investigate functional connectivity in a community sample of adolescents who reported psychotic symptoms (the extended psychosis phenotype). Method— This study investigated intrinsic functional connectivity (iFC) during resting-state functional magnetic resonance imaging (fMRI; rs-fMRI). Following screening in schools, 11 non- treatment seeking, youth with psychotic symptoms (aged 11–13) and 14 community controls participated in the study. Seed regions of interest comprised brain regions previously shown to exhibit aberrant activation during inhibitory control in adolescents with psychotic symptoms. Results— Relative to controls, adolescents with psychotic symptoms exhibited reduced iFC between regions supporting inhibitory control. Specifically, they showed weaker iFC between the right inferior frontal gyrus (IFG) and the cingulate, IFG and the striatum, anterior cingulate and claustrum, and precuneus and supramarginal gyrus. Conversely, the psychotic symptoms group exhibited stronger iFC between the superior frontal gyrus and claustrum and IFG and lingual gyrus. Conclusion— The present findings are the first to reveal aberrant functional connectivity in resting-state networks in a community sample of adolescents with psychotic symptoms and suggest that disruption in integration between distributed neural networks (particularly between
PUBLISHED
Keywords: Psychotic symptoms; Psychotic symptoms